Optimalisasi Muslim Friendly Tourism Dalam Meningkatkan Daya Tarik Wisata dan Kesejahteraaan Ekonomi Masyarakat Lokal di Pantai Slopeng Kabupaten Sumenep - Farisma, Azza; Sunariyah, Anik; Rohman, Abdur (Jurnal Iqtisaduna, 2023)
This study explores the impact of Muslim Friendly Tourism optimization at Slopeng Beach Sumenep, on tourism appeal and local economy. The research method used qualitative-descriptive approach involving government, tourism managers, stakeholders, business actors, local communities, and tourists. Slopeng Beach offers natural beauty with desert sand, clear sea water, and amazing sunset. Various nature tourism activities such as swimming, horse riding, ATV rental, camping, and playing sand. However, it faces challenges such as lack of Muslim-friendly facilities, sharia accommodation, low community awareness, promotion needs improvement, budget limitations, and maintenance of slum and unorganized MSMEs. Recommendations include improving facilities, Muslim-friendly services, sharia accommodation, socialization of Muslim-friendly tourism, use of social media and direct promotion to increase visits, communication forum formation, and collaboration with BPRS Bank to support MSMEs. This study provides insights on the importance of Muslim Friendly Tourism in enhancing tourism appeal and local economic welfare at Slopeng Beach.